Comparative benefits and harms of second generation antidepressants and cognitive behavioral therapies in initial treatment of major depressive disorder: systematic review and meta-analysis. (8th December 2015) - Amick, Halle R; Gartlehner, Gerald; Gaynes, Bradley N; Forneris, Catherine; Asher, Gary N; Morgan, Laura C; Coker-Schwimmer, Emmanuel; Boland, Erin; Lux, Linda J; Gaylord, Susan; Bann, Carla; Pierl, Christiane Barbara; et al.
Abstract : Study question What are the benefits and harms of second generation antidepressants and cognitive behavioral therapies (CBTs) in the initial treatment of a current episode of major depressive disorder in adults? Methods This was a systematic review including qualitative assessment and meta-analyses using random and fixed effects models. Medline, Embase, the Cochrane Library, the Allied and Complementary Medicine Database, PsycINFO, and the Cumulative Index to Nursing and Allied Health Literature were searched from January1990 through January 2015. The 11 randomized controlled trials included compared a second generation antidepressant CBT. Ten trials compared antidepressant monotherapy with CBT alone; three compared antidepressant monotherapy with antidepressant plus CBT. Summary answer and limitations Meta-analyses found no statistically significant difference in effectiveness between second generation antidepressants and CBT for response (risk ratio 0.91, 0.77 to 1.07), remission (0.98, 0.73 to 1.32), or change in 17 item Hamilton Rating Scale for Depression score (weighted mean difference, −0.38, −2.87 to 2.10). Similarly, no significant differences were found in rates of overall study discontinuation (risk ratio 0.90, 0.49 to 1.65) or discontinuation attributable to lack of efficacy (0.40, 0.05 to 2.91). Although more patients treated with a second generation antidepressant than receiving CBT withdrew from studies because of adverse events, the difference was not statistically significant (risk ratio 3.29, 0.42 to 25.72). No conclusions could be drawn about other outcomes because of lack of evidence. Results should be interpreted cautiously given the low strength of evidence for most outcomes. The scope of this review was limited to trials that enrolled adult patients with major depressive disorder and compared a second generation antidepressant with CBT, and many of the included trials had methodological shortcomings that may limit confidence in some of the findings. What this study adds Second generation antidepressants and CBT have evidence bases of benefits and harms in major depressive disorder. Available evidence suggests no difference in treatment effects of second generation antidepressants and CBT, either alone or in combination, although small numbers may preclude detection of small but clinically meaningful differences. Funding, competing interests, data sharing This project was funded under contract from the Agency for Healthcare Research and Quality by the RTI-UNC Evidence-based Practice Center. Detailed methods and additional information are available in the full report, available at http://effectivehealthcare.ahrq.gov/ .